ZEB1 recruits BRG1 to regulate airway remodelling epithelial‐to‐mesenchymal transition in asthma. Issue 5 (18th April 2022) - Wang, Ting; Peng, Bingming; Luo, Tingting; Tian, Daiyin; Zhao, Zhihua; Fu, Zhou; Li, Qubei
Abstract : New Findings: What is the central question of this study? The aim was to investigate the function of brahma‐related gene‐1 (BRG1) in airway remodelling epithelial‐to‐mesenchymal transition (EMT) of asthma and identify the transcription factor of BRG1 that binds to the protomer of E‐cadherin. What is the main finding and its importance? This study highlighted an important molecular mechanism involving chromatin remodelling factor BRG1 that played a crucial role in airway remodelling EMT of asthma and demonstrated that ZEB1 was the key transcription factor recruiting BRG1. This finding might offer new insights into gene‐based therapy for asthma. Abstract: Epithelial‐to‐mesenchymal transition (EMT) of airway remodelling happens in children with asthma. A reduction in the epithelial marker E‐cadherin is reported to be one of the initiating factors of EMT. Our previous study showed that chromatin remodelling factor brahma‐related gene‐1 ( BRG1 ) could regulate the expression of E‐cadherin indirectly. However, the transcription factor involved in the recruitment of BRG1 in asthma is unknown. Here, we studied the function of Brg1 in an ovalbumin‐induced asthma model [lung‐specific conditional Brg1 knockdown ( Brg1 −/− ) mice] and human bronchial epithelial 16HBE cells stably expressing BRG1 short hairpin RNA. Our results showed that Brg1 was involved in EMT in asthmatic mice by detecting the expression of EMT markers. We also identified that BRG1 participated in the transforming growth factor‐β‐induced EMT of 16HBE cells. We observed that zinc finger E‐box binding homeobox 1 (ZEB1) and BRG1 co‐localized in the EMT of TGF‐β‐induced 16HBE cells. Further results revealed that ZEB1 recruited BRG1 and bound to the promoter region (+3563/3715) to regulate E‐cadherin expression. Thus, ZEB1 might be the key transcription factor to recruit BRG1 in airway remodelling EMT of asthma and might be a new therapeutic target.